Non-Viral Nucleic Acid Delivery Strategies to the Central Nervous System - Tan, James-Kevin Y.; Sellers, Drew L.; Pham, Binhan; Pun, Suzie H.; Horner, Philip J. (Frontiers in Molecular Neuroscience, 2016)
With an increased prevalence and understanding of central nervous system injuries and neurological disorders, nucleic acid therapies are gaining promise as a way to regenerate lost neurons or halt disease progression. While more viral vectors have been used clinically as tools for gene delivery, non-viral vectors are gaining interest due to lower safety concerns and the ability to deliver all types of nucleic acids. Nevertheless, there are still a number of barriers to nucleic acid delivery. In this focused review, we explore the in vivo challenges hindering non-viral nucleic acid delivery to the central nervous system and the strategies and vehicles used to overcome them. Advantages and disadvantages of different routes of administration including: systemic injection, cerebrospinal fluid injection, intraparenchymal injection, and peripheral administration are discussed. Non-viral vehicles and treatment strategies that have overcome delivery barriers and demonstrated in vivo gene transfer to the central nervous system are presented. These approaches can be used as guidelines in developing synthetic gene delivery vectors for central nervous system applications and will ultimately bring non-viral vectors closer to clinical application.